Causal association between phenylalanine and Parkinson’s disease: a two-sample bidirectional mendelian randomization study - Li, Shiqing; Song, Huangcheng; Yu, Cong (Frontiers in Genetics, 2024)
Background: Research findings indicate a putative indirect or latent association between phenylalanine (Phe) and Parkinson's disease (PD). In this study, we aimed to analyze the causal relationship between Phe and PD by two sample Mendelian randomization (MR) analysis. Methods: In this study, the PD-related dataset and Phe-related dataset were downloaded from Integrative Epidemiology Unit (IEU) Open Genome-Wide Association Study (GWAS) database. Four algorithms (MR Egger, maximum likelihood, inverse variance weighting (IVW) and unweighted regression) were used to perform MR analysis. The sensitivity analysis (heterogeneity test, horizontal pleiotropy test and Leave-One-Out (LOO) analysis) was used to assess the reliability of MR analyses.In the forward MR analysis, Phe was a safety factor for PD (P value<0.05 and odds ratios (OR)<1). The results of reverse MR analysis showed that there was no causal relationship between PD and Phe (P value>0.05). In addition, sensitivity analysis showed that MR analysis was reliable.The results of this study revealed that Phe was a safety factor for PD, meaning that Phe reduced the risk of PD.